Peran Petugas Apron Movement Control (AMC) PT Angkasa Pura I Dalam Menangani Peningkatan Traffic Operasi Penerbangan Di Bandar Udara Internasional Juanda - Agung Yoga Hermawan; Septiyani Putri Astutik (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
The role of PT Angkasa Pura I Apron Movement Control (Amc) officers in handling the increase in flight operation traffic at Juanda International Airport, Surabaya, is to have an impact on the smooth running of flight operations, especially when there is an increase in flight operation traffic in the apron area. This research aims to 1). Understand the duties/roles of PT Angkasa Pura I Apron Movement Control (AMC) officers in handling the increase in Flight Operations Traffic at Juanda International Airport, Surabaya, East Java.2). Knowing the strategy and configuration used by the apron movement control (AMC) unit in handling increased flight operation traffic. 3). Knowing the obstacles faced by PT Angkasa Pura I Apron Movement Control (AMC) officers when experiencing an increase in Flight Operational Traffic at the International Airport Juanda Surabaya, East Java. This research was conducted at Juanda International Airport, Surabaya, this type of research uses qualitative methods, the data source in this research uses secondary data and primary data, data collection techniques use observation, interviews, documentation, literature study. Test the validity of the data using angulation techniques, data analysis techniques, data reduction, data presentation, verification and conclusions. The results of this research show that 1) handling the increase in flight operation traffic at Juanda International Airport, Surabaya, has an impact on smooth flight operations, especially when there is an increase in flight operation traffic in the apron area, 2) The configuration implemented is in accordance with MOSAMC/ KEP.DU.28/ OM.07/2021 which relates to Airside Service Operational Standards (Manual of Standard Airside Operation), which includes plotting aircraft parking, use of temporary parking stands, placement of aircraft parking outside of normal parking conditions, repositioning of aircraft parking , supervision of ground support equipment, aircraft parking guidance procedures using VDGS/ADGS.3). Experiencing a lack of handling efficiency and there could be a lack of maximum handling in dealing with flight operations traffic activities when it increases in the airside area/apron area both from terminal 1 and terminal 2 at Juanda International Airport, Surabaya, East Java.